Vascular endothelial growth factor exression in uterine cervical cancer: correlation with clinicopathologic characteristics and survival - Goncharuk, I.V.; Vorobjova, L.I.; Lukyanova, N.Yu.; Chekhun, V.F. (Experimental Oncology, 2009)
Aim: This retrospective study was performed to determine the vascular endothelial growth factor (VEGF) expression in cervical cancer cells, and to examine its correlation with clinicopathologic characteristics and survival of patients. Methods: Seventy-five paraffinembedded primary tumors were stained immunohistochemically for VEGF expression, which was analysed semiquantitatively. Results: The significant correlation between VEGF expression and stages of disease, as well as pelvic lymph node metastasis was observed. There were determined a negative correlations between VEGF expression in tumor cells and both overall and disease-free survival. Conclusion: VEGF expression in human cervical cancer may be used as a diagnostic parameter in the clinic. Our results are in accordance with literature data showing association of VEGF overexpression in tumor with a poorer patient survival.